MRI and MR angiography evaluation of pulsatile tinnitus: A focused, physiology‐based protocol. Issue 2 (15th December 2021) - Cummins, Daniel D.; Caton, Michael T.; Shah, Vinil; Meisel, Karl; Glastonbury, Christine; Amans, Matthew R.
Abstract: Background and Purpose: Pulsatile tinnitus (PT) is the subjective sensation of a pulse‐synchronous sound, most often due to a cerebrovascular etiology. PT can severely impact quality of life and may indicate a life‐threatening process, yet a timely and accurate diagnosis can often lead to effective treatment. Clinical assessment with a history and physical examination can often suggest a diagnosis for PT, but is rarely definitive. Therefore, PT should be evaluated with a comprehensive and targeted radiographic imaging protocol. MR imaging provides a safe and effective means to evaluate PT. Specific MR sequences may be used to highlight different elements of cerebrovascular anatomy and physiology. However, routine MR evaluation of PT must comply with economic and practical constraints, while effectively capturing both common and rarer, life‐threatening etiologies of PT. Methods: In this state‐of‐the‐art review, we describe our institutional MR protocol for evaluating PT. Results: This protocol includes the following dedicated sequences: time‐of‐flight magnetic resonance angiography; arterial spin labeling; spoiled gradient recalled acquisition in the steady state; time‐resolved imaging of contrast kinetics; diffusion weighted imaging, and 3‐dimensional fluid‐attenuated inversion recovery. Conclusions: We describe the physiologic and clinical rationale for including each MR sequence in a comprehensive PT imaging protocol, and detail the role of MR within the broader evaluation of PT, from clinical presentation to treatment.